Empowering Tourism Village Managers through Digital Promotion Training: Evidence from Cibodas Village - Vigory Gloriman Manalu; Sutarman; Astri Anggelia (PT. Berkah Digital Teknologi, 2025)
This community service program aimed to strengthen the digital marketing capabilities of tourism managers and local entrepreneurs in Cibodas Village, Bandung Regency, as part of efforts to promote rural tourism and support sustainable development. The initiative addressed the limited digital literacy among stakeholders, which has hindered effective utilization of social media and online platforms for destination promotion. Using a participatory approach, the program involved three stages: preparation, implementation, and evaluation. Training modules covered digital promotion strategies, creative content development, persuasive copywriting using the AIDA framework, and practical design skills through Canva, complemented by sessions on Google Trends and digital ethics. The workshop, held on 29 July 2025, resulted in improved understanding of branding principles and enhanced technical skills for producing visually consistent and persuasive promotional materials. Participants demonstrated increased confidence in managing social media channels and began establishing informal organizational roles for content planning and administration. Despite challenges such as limited internet connectivity and time constraints, adaptive strategies—such as content batching and shared repositories—were introduced. To ensure sustainability, the program recommends continuous mentoring, integration of performance indicators (e.g., engagement rate, reach, conversion), and advanced training on paid advertising and multi-platform optimization. These outcomes indicate that structured capacity-building initiatives can effectively bridge the digital gap in rural tourism, foster community empowerment, and contribute to local economic resilience. Abstrak Program pengabdian masyarakat ini bertujuan untuk memperkuat kemampuan pemasaran digital para pengelola pariwisata dan pengusaha lokal di Desa Cibodas, Kabupaten Bandung, sebagai bagian dari upaya mempromosikan pariwisata pedesaan dan mendukung pembangunan berkelanjutan. Inisiatif ini mengatasi keterbatasan literasi digital di kalangan pemangku kepentingan, yang telah menghambat pemanfaatan media sosial dan platform daring secara efektif untuk promosi destinasi. Dengan menggunakan pendekatan partisipatif, program ini melibatkan tiga tahap: persiapan, implementasi, dan evaluasi. Modul pelatihan mencakup strategi promosi digital, pengembangan konten kreatif, penulisan iklan persuasif menggunakan kerangka kerja AIDA, dan keterampilan desain praktis melalui Canva, dilengkapi dengan sesi tentang Google Trends dan etika digital. Lokakarya yang diadakan pada 29 Juli 2025 ini menghasilkan peningkatan pemahaman tentang prinsip-prinsip branding dan peningkatan keterampilan teknis untuk menghasilkan materi promosi yang konsisten secara visual dan persuasif. Para peserta menunjukkan peningkatan kepercayaan diri dalam mengelola saluran media sosial dan mulai membangun peran organisasi informal untuk perencanaan dan administrasi konten. Terlepas dari tantangan seperti konektivitas internet yang terbatas dan kendala waktu, strategi adaptif—seperti pengelompokan konten dan repositori bersama—diperkenalkan. Untuk memastikan keberlanjutan, program ini merekomendasikan pendampingan berkelanjutan, integrasi indikator kinerja (misalnya, tingkat keterlibatan, jangkauan, konversi), dan pelatihan lanjutan tentang periklanan berbayar dan optimasi multi-platform. Hasil ini menunjukkan bahwa inisiatif peningkatan kapasitas yang terstruktur dapat secara efektif menjembatani kesenjangan digital dalam pariwisata pedesaan, mendorong pemberdayaan masyarakat, dan berkontribusi pada ketahanan ekonomi lokal.